Legal and ethical behaviour in library and information science students’ research supervision in Nigeria (2016)
Research is at the heart of Library and Information Science (LIS) education across the world. The essence of research is to make new discoveries and extend the frontiers of knowledge in a given field with a view to finding solutions to societal problems. In the LIS field, research has brought about tremendous development to principles and practice which, in turn, has impacted positively on the way information resources are acquired, processed and made accessible for developmental purposes. Critical to successful research outcomes is supervision, particularly for a student researcher carrying out research work in partial fulfilment of the requirements for the award of a degree. The relationship of the parties in research supervision is governed by legal and ethical considerations. There is a measure of legal and ethical behaviour expected of both the supervisor and the supervisee. This paper, therefore, discusses and makes an exposition of the legal and ethical behaviour expected in research supervision. It concludes by recognising the need for and recommends compliance with legal and ethical standards in LIS research supervision in Nigeria.